Estratégia de saúde da família e o atendimento aos adolescentes - Santos, Bibiana Ramos dos (2011)
The aim of this research was to know the demands identified by health care team professionals of Family Health Care Strategy, focusing on adolescence. Such study contemplates on its theoretical review a presentation of the Health System and the Family Health Care Strategy, as well as the public policies for adolescents proposed by the Health Ministry (PROSAD). There is a specific chapter about adolescence, in which changes experienced in such period of development are approached, including physical, psychic and social aspects, as well as the importance of the family relationships as regards the adolescents. Such study aimed to understand, through the Bioecological Theory of Human Development, the relation between the adolescent and his context, establishing interferences among microsystems and their effects on the adolescent‟s health. In order to reach the aim of the study, a qualitative approach was used. Data collection consisted of semi-structured interviews carried out with professionals of five teams of Family Health Care Strategy in Santa Maria/RS. Results were understood through the analysis of multiple cases and analyzed through content analysis. The reports of the professionals indicate the fragility of actions directed to the adolescent public, but also point out important problems presented in such group. Among them, the results highlight pregnancy in adolescence, violence, drugs and family problems. The professionals point out the absence of projects directed to the adolescent public, what could increase the risk concerning the problems previously described. The health care professionals have no knowledge of the existence of Adolescent Health Care Program (PROSAD), and such aspect enables understanding the difficulties referred concerning assistance of the adolescent public. Moreover, aspects regarding working instability related to the maintenance of the health care teams were pointed out by the professionals. Such aspects interfere on the bonds established with the community, as well as on the investment concerning new actions and/or projects. The final considerations highlight the importance of making improvements in the working process of the teams of Family Health Care Strategy, emphasizing the proposal to strengthen the implementation of ideas present in PROSAD, which includes the main questions highlighted by the professionals as part of their communities. Without the consolidation of specific actions for the adolescents, risks seem to increase within such group. Thus, health care promotion and prevention become increasingly urgent and necessary.